2004
DOI: 10.1007/s11176-005-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in AB5-NH3 systems

Abstract: Treatment of intermetallic compounds LaNi 5 and SmCo 5 with ammonia (initial ammonia pressure 0.630.7 MPa) in the presence of 10 wt % NH 4 Cl as an activator results in hydrogenation of these compounds or, in the case of SmCo 5 , in disproportionation to form Sm 2 Co 7 H x . In some cases, the intermetallic matrix decomposes under this treatment.Intermetallic compounds AB 5 (A = La, Sm; B = Ni, Co) are used as metal hydride accumulators of hydrogen and for production of permanent magnets [1].Intermetallic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Metals of Group V, including vanadium, are activated at temperatures from 573 to 1273 K in vacuum with D < 1.3 × 10 −4 to 1 Pa [5][6][7].…”
Section: Activation Of Vanadiummentioning
confidence: 99%
“…Metals of Group V, including vanadium, are activated at temperatures from 573 to 1273 K in vacuum with D < 1.3 × 10 −4 to 1 Pa [5][6][7].…”
Section: Activation Of Vanadiummentioning
confidence: 99%
“…It was found that the direct addition of oxygen to the hydride lattice not only varies the stoichiometry by stabilizing the oxygen positions in the crystal lattice, but also expands the possibilities of chemical control of the structural and electronic properties of such a modified metalÀhydride system. [4][5][6][7][8][9][10] The effect of partial oxidation makes the variation of the crystal structure stable, as chemical interactions form a reconfiguration of the valence charges that provides a new minimum of free energy. [3,10] Compared with the initial metal hydride, the ground state of the oxyhydride system exhibits better compositional and structural stability; its macroscopic mechanical properties are similar to those of complex crystalline oxides.…”
Section: Introductionmentioning
confidence: 99%
“…An oxyhydride is a complex inorganic chemical compound in which the rare‐earth or transition metal is a cation that is balanced by two adjacent anions, normalO2 and normalH, forming different compositional ratios. [ 1–3 ] The development of oxyhydrides began more than 20 years ago [ 4–7 ] as an effort to improve some key properties of transition metal hydrides. It was found that the direct addition of oxygen to the hydride lattice not only varies the stoichiometry by stabilizing the oxygen positions in the crystal lattice, but also expands the possibilities of chemical control of the structural and electronic properties of such a modified metal−hydride system.…”
Section: Introductionmentioning
confidence: 99%
“…The central issue of how oxygen as an oxidant triggers a number of functional transformations in transition‐metal hydrides became a center of attention of several investigations (a short review can be found in ref. []).…”
Section: Introductionmentioning
confidence: 99%